2018
DOI: 10.1097/md.0000000000009930
|View full text |Cite
|
Sign up to set email alerts
|

Starting of biological disease modifying antirheumatic drugs may be postponed in rheumatoid arthritis patients with multimorbidity

Abstract: The objective of this study was to assess the frequency of comorbidities and multimorbidities in rheumatoid arthritis (RA) patients under biologic therapy and their effects on biological disease modifying antirheumatic drugs (DMARDs) choice, timing, and response.Hacettepe University Biologic Registry (HUR-BIO) is single center biological DMARD registry. Cardiovascular, infectious, cancer, and other comorbidities were recorded with face to face interviews. Multimorbidity is defined as >1 comorbidity. Disease du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Comorbidities were not examined as possible predictors of disease activity in this analysis. Previous registry analyses have shown that the presence and number of comorbid conditions in RA are associated with lower chance of achieving remission [23,40]. Assessment of outcomes of biologic therapy in real-world practice remains challenging due to the varied trajectory of disease across patients and the lack of a long-term control group, because patients whose disease progresses beyond nonbiologic DMARD management typically receive biologics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidities were not examined as possible predictors of disease activity in this analysis. Previous registry analyses have shown that the presence and number of comorbid conditions in RA are associated with lower chance of achieving remission [23,40]. Assessment of outcomes of biologic therapy in real-world practice remains challenging due to the varied trajectory of disease across patients and the lack of a long-term control group, because patients whose disease progresses beyond nonbiologic DMARD management typically receive biologics.…”
Section: Discussionmentioning
confidence: 99%
“…Registry study data can be used to examine whether longer-term exposure to a biologic maintains the benefits for reduced disease activity and function impairment. Previous analyses of registry data have shown that RA patients who respond to biologic therapy in the first 6-12 months usually experience persistent benefits if they continue biologic therapy for several years [15][16][17][18][19][20][21][22][23][24]. The objective of this analysis was to examine the effect of cumulative exposure to biologics on patient outcomes over time, as well as predictors for improvement in outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of comorbidities 1,21 and of obesity 7 in patients with RA and the association between comorbidity and RA disease progression 22 have led to extensive investigation into the potential effect of comorbid conditions and of obesity on disease-modifying antirheumatic drug (DMARD) efficacy. Patients with a higher comorbidity burden may be less likely to start a biologic agent early in their disease course 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of comorbidities 1,21 and of obesity 7 in patients with RA and the association between comorbidity and RA disease progression 22 have led to extensive investigation into the potential effect of comorbid conditions and of obesity on disease-modifying antirheumatic drug (DMARD) efficacy. Patients with a higher comorbidity burden may be less likely to start a biologic agent early in their disease course 21 . Obesity has also been associated with poorer clinical outcomes in patients with RA, despite DMARD therapy, and efficacy of tumor necrosis factor inhibitors is negatively affected by patients' weight 10,12,13,16,23,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesize that these patients might attach less importance to RA management because of the burden of comorbidities and thus may not visit their rheumatologists. On the other hand, rheumatologists may also be reluctant to use targeted agents for fear of complications related to comorbidities 10 . Although understandable, this type of reasoning could be counterproductive given that systemic inflammation associated with RA may contribute to comorbidities, such as cardiovascular diseases, for instance.…”
mentioning
confidence: 99%